2021
DOI: 10.1021/acsanm.0c03080
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Field Emitters on the Basis of Pd-Adsorbed ZnO Nanostructures by Photochemical Method

Abstract: In this investigation, field electron emission (FE) performances of pure zinc oxide (ZnO) nanorod (NR) arrays and ZnO NRs with adsorbed palladium nanoparticles (Pd-ZnO) were explored under high-vacuum conditions. The nanostructures were successfully grown on substrates via a simple hydrothermal method (HM) and photochemical synthesis process. After characterizing the structural and crystal results of the as-grown samples, it was found that all NR structures were observed to be single crystals and presented str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 35 publications
(32 reference statements)
1
2
0
Order By: Relevance
“…In other words, a large number of OH – ions cause an additional negative bias on the gate; thus, the I DS decreases when the pH value increases. When the I DS was 0.3 mA, the voltage sensitivity and linearity of the Z@Ag-0 nanostructures were 24.77 mV/pH and 0.975, respectively, and the voltage sensitivity and linearity of the Z@Ag-1 nanostructures were 59.06 mV/pH and 0.996, respectively, as shown in Figure g,h. Based on the above results, it can be found that the ZnO pH sensor decorated with Ag NPs has good electrical properties and pH-sensing performances, which suggests that the density of Ag NPs can create more surface-active sites for H + or OH – sensing. That is to say, the Ag NPs can transmit sensing signals more easily; this phenomenon is similar to a previous report . The V T,EGFET could be defined and expressed as the following equation V normalT , E G F E T = V normalT , M O S F E T φ M / q E normalR normalE normalF + χ normalS normalo normall ψ where V T,MOSFET is the threshold voltage of the MOSFET, φ M is the metal gate work function of the reference electrode, q is the electron charge, E REF is the potential of the reference, χ Sol is the surface dipole potential of the electrolytic solution, and ψ is the surface potential between the interface of the pH buffer solution and the sensing material.…”
Section: Results and Discussionsupporting
confidence: 74%
“…In other words, a large number of OH – ions cause an additional negative bias on the gate; thus, the I DS decreases when the pH value increases. When the I DS was 0.3 mA, the voltage sensitivity and linearity of the Z@Ag-0 nanostructures were 24.77 mV/pH and 0.975, respectively, and the voltage sensitivity and linearity of the Z@Ag-1 nanostructures were 59.06 mV/pH and 0.996, respectively, as shown in Figure g,h. Based on the above results, it can be found that the ZnO pH sensor decorated with Ag NPs has good electrical properties and pH-sensing performances, which suggests that the density of Ag NPs can create more surface-active sites for H + or OH – sensing. That is to say, the Ag NPs can transmit sensing signals more easily; this phenomenon is similar to a previous report . The V T,EGFET could be defined and expressed as the following equation V normalT , E G F E T = V normalT , M O S F E T φ M / q E normalR normalE normalF + χ normalS normalo normall ψ where V T,MOSFET is the threshold voltage of the MOSFET, φ M is the metal gate work function of the reference electrode, q is the electron charge, E REF is the potential of the reference, χ Sol is the surface dipole potential of the electrolytic solution, and ψ is the surface potential between the interface of the pH buffer solution and the sensing material.…”
Section: Results and Discussionsupporting
confidence: 74%
“…Young and Y. L. Chu developed a system of Pd nanoparticle decorated ZnO quantum dots and quantum wires. 34 In their case, including Pd did not have a marked effect in changing the turnon eld, but the decorated system showed more than a 100% increase in the enhancement factor. Jun Chen obtained a very high emission current of 20 mA et al from their developed system of indium-doped ZnO.…”
Section: Introductionmentioning
confidence: 89%
“… 31 Though this has fundamental importance, it lacks practical application. The work in 34 showed that including Pd did not affect the emission characteristics much. Though doped ZnO gives a very interesting and useful FE result, it has the same drawback with a high thermal energy required in the synthesis process.…”
Section: Introductionmentioning
confidence: 97%